Financial Analysis of Feasibility Development Nur Hidayah Hospital Become Type C Hospital - Khoirunnisa, Estianna; Bastian, Indra (Academic Hospital Journal, 2022)
Background: The development of a business unit is based on assessments given by competent parties both internally and externally. Nur Hidayah Hospital received a recommendation to become a Type C hospital from the Bantul District Health Office, the Association of Indonesian Hospitals (PERSI) DIY Region, and the DIY Hospital Supervisory Agency (BPRS) during visitation for the purposes of extending the operational permit of the Hospital in 2020.Objective: To determine the financial analysis of the feasibility of developing Nur Hidayah Hospital into a type C hospital.Design: This research is a qualitative descriptive method with a case study design. The data was taken at Nur Hidayah Hospital in September-October 2021. The data was obtained using questionnaires and secondary data from internal hospital. Data is processed by presentation of data and withdrawal of conclusions.Results: Based on data analysis, the Net present value (NPV) is 45,162,803,090 or positive value, with an internal rate of return (IRR) 28,48% and a payback period (PP) of 7 years and 2 months.Conclusions: The development of Nur Hidayah Hospital into a Type C hospital is feasible. The results of this study can be used by the management and the Nur Hidayah Foundation to develop the Nur Hidayah Hospital as planned.